TYPES OF DICTIONARIES (Ustozlar uchun, 2025)
This article looks at the idea and types of dictionaries as important tools in language learning, translation, and linguistic research. Dictionaries serve many functions including providing meanings, pronunciation, grammar information, and usage examples. The study examines main types of dictionaries like monolingual, bilingual, learner’s, encyclopedic, specialized, etymological, pronouncing, and electronic dictionaries. Each type is discussed in terms of its purpose, structure, and relevance to different users.